Analytical Study on Limiting Value of Shape Factor of Vertically Loaded Anchors in Saturated Soft Clay - Guoqi Xing; Yupeng Cao; Baoliang Zhang; Jian Li; Dapeng Li (Advances in Civil Engineering)
The limiting values of shape factors are an important parameter for vertically loaded anchors (VLAs) at the deep-embedded depth, which influence the ultimate embedded depth and the maximum load-bearing capacity. The limiting values of load-bearing coefficients of VLAs which have different aspect ratios and different areas of fluke are obtained using the finite-element method. Furthermore, based on the expression of shape factors, the limiting values of shape factors of VLAs with different aspect ratios and different areas of a fluke are calculated. The influence of the aspect ratios and areas of fluke of VLAs on the shape factors is investigated. In addition, the effect of the shape factors of VLAs on the ultimate embedded depth and the maximum load-bearing capacity at the ultimate embedded depth is also studied. The results show that when the area of a fluke of VLAs is the same, decreasing the aspect ratio of a fluke can decrease the limiting value of shape factors; when the length of the fluke is constant, the area of the fluke has little influence on the limiting values of shape factors of VLAs. When the area of the fluke of VLAs is the same, the normalized ultimate embedded depth increases almost linearly with increasing the limiting value of shape factors and the maximum load-bearing capacity increases with increasing the limiting value of shape factors. The results can contribute to the design of the shape of a fluke of VLAs in soft clay.